Philippians in the Greek New Testament for the English reader. - Wuest, Kenneth S. (Grand Rapids, MI Eerdmans, 1948)
Includes bibliographical references and index.
Donated by Mrs F. Hunter.
Keywords: Bible. N.T. Philippians -- harmonies; Bible. N.T. Colossians -- commentaries